Dynamics of VEGF-A binding at VEGFR2 and NRP1 - Peach, Chloe J (2020)
Vascular Endothelial Growth Factor A (VEGF-A) is a key mediator of angiogenesis, a process dysregulated in tumour development. Alternative splicing of the Vegfa gene leads to distinct endogenous VEGF-A isoforms with differential signalling and expression. These include pro-angiogenic VEGF165a, ‘anti-angiogenic’ VEGF165b and freely diffusible VEGF121a. VEGF-A primarily signals via its cognate receptor tyrosine kinase (RTK), VEGF Receptor 2 (VEGFR2). Signalling can be potentiated by its co-receptor Neuropilin-1 (NRP1), a transmembrane protein also found at high levels in malignant tumours. Despite numerous approved anti-cancer therapeutics targeting VEGF-A/VEGFR2 signalling, there is limited quantitative pharmacological understanding of VEGF-A isoforms at full-length VEGFR2 or NRP1 in living cells. This thesis explored the spatial and temporal dynamics of ligand binding to VEGFR2 and its co-receptor NRP1.